Strategi Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Kinerja Pendidik di SDN 15 Banyuasin III : Principal Leadership Management Strategy in Improving the Quality of Educator Performance at SDN 15 Banyuasin III - Susi Lusiani; Bukman Lian; Syaiful Eddy (ITScience (Information Technology and Science), 2025)
This study aims to describe the principal's leadership management strategy in improving the quality of educator performance at SDN 15 Banyuasin III. The study focuses on the principal's actions in managing school resources, distributing teacher workloads fairly, and empowering teachers to improve professionalism and learning quality. This study uses a qualitative method with a naturalistic descriptive approach. The research subjects comprised one principal and 12 teachers who served as key informants. The data was collected through in-depth interviews, direct observation for 1 month (December 20, 2024–January 20, 2025), and analysis of school documents. Data were analyzed thematically to identify patterns of leadership strategies applied. The results show that the principal applies a transformational and participatory leadership style by conducting routine training at least twice a semester, conducting academic supervision every month, providing constructive feedback after the learning process, and empowering teachers through personal mentoring. The main obstacles faced include limited technology-based learning facilities, high teacher administrative workloads, and resistance from some teachers to change. However, principals can overcome these challenges through adaptive strategies, such as collaborating with the school committee, flexibly dividing tasks, and optimizing the school budget. These findings confirm that effective principal leadership is crucial in creating a productive work environment and driving sustainable improvements in educator performance.